ผลของการสอนภาษาอังกฤษโดยใช้แนวคิดระหว่างวัฒนธรรม ที่มีต่อความตระหนักระหว่างวัฒนธรรมของนักเรียนมัธยมศึกษาตอนปลาย - เชยชัยภูมิ ปทุมา; คชเสนี จันทร์ทรงกลด (An Online Journal of Education, 2014)
แนวคิดระหว่างวัฒนธรรมได้มีบทบาทมากขึ้นในการศึกษาภาษาอังกฤษและความตระหนักระหว่างวัฒนธรรมก็เป็นองค์ประกอบสำคัญในการพัฒนาบุคคลไปสู่การเป็นพลเมืองโลก ดังนั้น งานวิจัยนี้จึงมีจุดมุ่งหมายเพื่อศึกษาผลของการใช้แนวคิดระหว่างวัฒนธรรมในการสอนภาษาอังกฤษที่มีต่อความตระหนักระหว่างวัฒนธรรมของนักเรียนชั้นมัธยมศึกษาตอนปลาย และเพื่อศึกษาความคิดเห็นของนักเรียนที่มีต่อการสอนนี้ งานวิจัยนี้ได้เก็บข้อมูลวิจัยเชิงปริมาณและเชิงคุณภาพจากนักเรียนชั้นมัธยมศึกษาปีที่ 5 จำนวน 31 คน ในการทดลอง 14 สัปดาห์ สถิติที่นำมาใช้ในการวิเคราะห์ความแตกต่างระหว่างคะแนนเฉลี่ยจากแบบวัดความตระหนักระหว่างวัฒนธรรมก่อนและหลัง และแบบสอบถามตามแบบลิเคิร์ต 5 ระดับ ได้แก่ Paired sample t-test ค่าเฉลี่ย และค่าเบี่ยงเบนมาตรฐาน ส่วนข้อมูลเชิงคุณภาพใช้การวิเคราะห์เนื้อหาเพื่อศึกษาความคิดเห็นของนักเรียนจากแบบสอบถามปลายเปิดและบันทึกการเรียนรู้ ผลการวิจัยพบว่า 1) มีความแตกต่างระหว่างคะแนนเฉลี่ยจากแบบวัดความตระหนักระหว่างวัฒนธรรมก่อนและหลังอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 และมีค่าอิทธิพลเฉลี่ย 0.94 ซึ่งหมายถึงมีค่าอิทธิพลมาก นักเรียนยังแสดงความตระหนักระหว่างวัฒนธรรมในบันทึการเรียนรู้ด้วย 2) จากแบบสอบถามและบันทึกการเรียนรู้ นักเรียนรายงานถึงทัศนคติแง่บวกที่มีต่อการสอนนี้ ดังนั้นนักเรียนชั้นมัธยมศึกษาตอนปลายจึงพัฒนาความตระหนักระหว่างวัฒนธรรมหลังจากการนำแนวคิดระหว่างวัฒนธรรมไปปฏิบัติใช้ในการสอนภาษาอังกฤษ Intercultural approach has played a bigger role in English Language Education and intercultural awareness is a fundamental element to advancing individuals towards global citizenship. Therefore, this study aimed to examine the effects of English instruction using intercultural approach on the intercultural awareness of upper secondary school students and to investigate their opinions towards the instruction. The quantitative and qualitative data were collected from 31 eleventh grade students in the 14-week experiment. The paired sample t-test, means, and standard deviation were applied to investigate the differences between the means scores from the pre- and post- intercultural awareness tests and from a five-point Likert scale questionnaire. For the qualitative data, content analysis was used to examine the opinions of the students from the open-ended questionnaire and learner logs. The results revealed that: 1) There was a significant difference between the mean scores from the pre- and post- intercultural awareness test at the significant level of .05 and the effect size was at 0.94 which indicated a large effect. 2) Students reported positive attitudes towards the instruction through the questionnaire and learner logs. Consequently, upper secondary school students improved their intercultural awareness after the implementation of the intercultural approach in English instruction.